Comorbid symptoms of depression and musculoskeletal pain and risk of long term sickness absence - Ole Melkevik; Thomas Clausen; Jacob Pedersen; Anne Helene Garde; Andreas Holtermann; Reiner Rugulies (BMC, 2018)
Abstract Background Symptoms of depression and musculoskeletal pain have both been found to be associated with increased risk of long term sickness absence (LTSA). The comorbidity between depression and pain i.e. simultaneous presence of both symptoms, is well established in the literature. The aim for the current investigation was to investigate whether the presence of comorbid pain influences the associations between depressive symptoms and LTSA or if the presence of comorbid depressive symptoms influences associations between musculoskeletal pain and LTSA. Methods A sample of 6572 Danish female health care workers responding to a questionnaire about health and working conditions were followed up in a national register of social transfer payments (DREAM) for 550 days. We estimated the risk for LTSA of four weeks or more, associated with depressive symptoms and number of musculoskeletal pain locations using a Cox proportional hazards model allowing multiple observations per individual. We conducted a test for multiplicative interaction between musculoskeletal pain locations and depressive symptoms, and presented stratified regression models to facilitate the interpretation of the results. Results The severity of depressive symptoms was correlated with the number of pain locations reported (Spearman's rho = .24, p < 0.001). We found a significant multiplicative interaction between depressive symptoms and musculoskeletal pain in predicting the risk of LTSA. Depressive symptoms and number of musculoskeletal pain locations were associated with increased risk of LTSA for individuals who did not have comorbid symptoms. However, we found no significant associations between the two predictors and LTSA among participants who reported comorbid symptoms. Conclusions The risk of LTSA associated with depressive symptoms and musculoskeletal pain appears to be moderated by the presence of comorbid symptoms. The modified risk for LTSA among workers with comorbid symptoms requires further investigation.